ANALISIS TINGKAT RISIKO KREDIT PADA PT. BANK RAKYAT INDONESIA (PERSERO) - Liya Saputri (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2025)
This study aims to analyze the level of bank credit risk whether the bank is included in the healthy or unhealthy category according to Bank Indonesia's provisions. In addition, by analyzing the level of credit risk, the level of bank financial health can also be determined from year to year. The purpose of compiling this thesis is to determine the level of credit risk as reviewed from Non Performing Loan (NPL) at PT. Bank Rakyat Indonesia (Persero) Tbk. Sinjai Branch. This study was conducted using a simple regression method, namely analyzing the collectibility of Non Performing Loan (NPL) of Bank Rakyat Indonesia, Sinjai Branch. Based on the results of the study, it was concluded that the NPL credit of Bank Rakyat Indonesia, Sinjai Branch for four years (2016-2019) experienced ups and downs every year. However, when viewed from the average percentage of the risk level of Bank Rakyat Indonesia, Sinjai Branch is below the provisions of Bank Indonesia, which is 5% for the low credit category with an average amount of 1.30%. This means that the Non Performing Loan (NPL) of PT. Bank Rakyat Indonesia Sinjai branch for four years (2016-2019) is classified as low according to Bank Indonesia regulations.